Pluralisme Hukum dalam Penentuan Ramadan: Otoritas Kitab Matla’ul Badrayn sebagai Living Law di Masyarakat Indonesia.: Legal Pluralism in Determining the Start of Ramadan: The Authority of the Book Matla'ul Badrayn as "Living Law" in Indonesian Society. - Muhammad Khalil Mubarraq; Ismail Ismail; Laiyina Ukhti (QISTHOSIA : Jurnal Syariah dan Hukum, 2026)
Determining the beginning of Ramadan in Indonesia is frequently marked by tension between the state regulatory authority and traditional religious texts. This article analyzes the Kitab Matla' al-Badrayn wa Majma' al-Bahrayn by Sheikh Muhammad bin Ismail al-Fathani, which has transformed from classical literature into a living law within the Muslim community of the Archipelago (Nusantara). Employing a socio-legal approach, this study examines how theological compliance with the text, specifically page 60, which prescribes methods for determining Ramadan through istikmal, rukyah hilal, isbat hilal, and customary signs, challenges the hegemony of the national calendar unification based on MABIMS astronomical criteria. The findings indicate that the community's continued adherence to the local matla' territorial limit of 24 farsakh is a unique phenomenon. Although information technology enables the instant distribution of rukyah hilal news beyond physical boundaries, a segment of society continues to reject long-distance rukyah results that transcend textual stipulations. This underscores that for traditional society, legal certainty in worship is determined more by steadfast conviction in the turats heritage than by the administrative rationality of Wilayatul Hukmi proposed by the state. This article concludes that the reality of legal pluralism cannot be negated solely through a technocratic approach. The existence of Matla' al-Badrayn as a moral compass demands that the state acknowledge differences in month-determination methods as logical consequences of diversity within Islamic legal epistemology. These differences must be managed through constructive dialogue rather than coercive unification.